Spontaneous Heterotopic Pregnancy: A Case Report - Ahmed, Getachew; Mekonnen Assefa, Endalkachew (Ethiopian Journal of Reproductive Health, 2020)
ABSTRACT INTRODUCTION: Heterotopic pregnancy refers to the presence of simultaneous pregnancies at two or more different implantation sites; commonly both intrauterine and extrauterine gestation. It is a rare and life-threatening condition which is difficult to diagnose and easily missed. We report an extremely rare case of heterotopic pregnancy after natural conception with cardiac activity noted on sonography in both the intrauterine and the ectopic pregnancy. CASE PRESENTATION A 38 years old gravida 2 para 1 mother diagnosed with heterotopic pregnancy despite lack of any notable risk factors at a gestational age of 11weeks and 6 days. Trans-vaginal ultrasound showed alive intrauterine pregnancy and right adnexal ectopic pregnancy with a heartbeat. She underwent exploratory laparotomy and right salpingectomy was done and discharged home with a stable clinical condition; and had uneventful antenatal visits. She delivered by emergency C- section at 39 weeks & 3 days gestation for an indication of non-reassuring fetal heart rate pattern. CONCLUSION: This un-common case demonstrates the possibility of occurrence of natural heterotopic pregnancy and clinical detection helped for a good maternal and fetal outcome. Keywords: Ectopic pregnancy; Heterotopic pregnancy, Spontaneous